2016
DOI: 10.3390/pharmacy4010006
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Level Practice Education: UK Critical Care Pharmacists’ Opinions in 2015

Abstract: National UK standards for critical care highlight the need for clinical pharmacists to practice at an advanced level and above. The aim of this research paper was to describe the views of UK critical care pharmacists on the current provision of Advanced Level Practice (ALP) education and accreditation. It sought to identify whether there is a need for a national or regional training programme. A questionnaire was delivered electronically targeting UK critical care pharmacists. Whilst the response rate was low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…This supports the results of a survey of critical care pharmacists by Warin et al [10] and is typical of other health-care professionals [20,21,22]. Work-based learning was facilitated by two different communities of practices, critical care and pharmacy.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This supports the results of a survey of critical care pharmacists by Warin et al [10] and is typical of other health-care professionals [20,21,22]. Work-based learning was facilitated by two different communities of practices, critical care and pharmacy.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, of those non-ALP pharmacists approximately a third did not have access to an ALP pharmacist at their institution [9]. Warin et al [10] surveyed critical care pharmacists and found they felt that there were no suitable training programmes to help them to develop ALP. The key recommendation from the survey was a requirement to develop a national or regional ALP training programme [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike in the USA [ 34 ], the UK does not yet have a recognised critical care pharmacist training programme. The need for [ 35 ], and format of [ 9 ], an advanced-level training programme for critical care pharmacists has been identified, but national delivery and credentialling remains a challenge. Greater organisational workstream alignment between pharmacy bodies and intensive care specialty groups can aid pharmacy service developments.…”
Section: Resultsmentioning
confidence: 99%
“…1 Supporting systems such as face-to-face peer discussion, mentorship and work-based learning are practitioner development tools that need expansion and formalising to optimise the pharmacist's skills. 4 Some of this is required by the revalidation for pharmacy professionals process which formally starts in 2018. 5 A high proportion of critical care pharmacists are also prescribers, 6 and this is set to become a standard feature.…”
Section: Trainingmentioning
confidence: 99%